2013
DOI: 10.1021/bc300542z
|View full text |Cite
|
Sign up to set email alerts
|

Use of Novel Mutant Galactosyltransferase for the Bioconjugation of Terminal N-Acetylglucosamine (GlcNAc) Residues on Live Cell Surface

Abstract: Based on the crystal structure of bovine β4Gal-T1 enzyme, mutation of a single amino acid Y289 to L289 (Y289L) changed its donor specificity from Gal to N-acetyl-galactosamine (GalNAc). A chemoenzymatic method that uses GalNAc analogues like GalNAz or 2-keto-Gal as sugar donors with the enzyme Y289LGal-T1 has identified hundreds of cytosolic and nuclear proteins that have O-GlcNAc modifications. To avoid potential cytotoxicity at Mn2+ concentrations required to selectively modify GlcNAc residues on the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…5 This process, for which we coined the term SEEL (selective exoenzymatic labeling), takes advantage of recombinant glycosyltransferases and a corresponding functionalized nucleotide sugar to install chemical reporters on cell surface acceptor glycans. For example, we have demonstrated that recombinant ST6Gal1 sialyltransferase and CMP-Neu5Ac9N 3 ( 1 ) can be exploited for the selective labeling of N -linked glycans of living cells with azido-modified sialic acid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 This process, for which we coined the term SEEL (selective exoenzymatic labeling), takes advantage of recombinant glycosyltransferases and a corresponding functionalized nucleotide sugar to install chemical reporters on cell surface acceptor glycans. For example, we have demonstrated that recombinant ST6Gal1 sialyltransferase and CMP-Neu5Ac9N 3 ( 1 ) can be exploited for the selective labeling of N -linked glycans of living cells with azido-modified sialic acid.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have demonstrated that recombinant ST6Gal1 sialyltransferase and CMP-Neu5Ac9N 3 ( 1 ) can be exploited for the selective labeling of N -linked glycans of living cells with azido-modified sialic acid. 5g,6 The attraction of the SEEL approach is that it only labels a specific class of cell surface molecules (e.g., N - vs O -glycans) and does not rely on feeding with metabolic substrates that must compete with natural sugar precursor pools. In light of the direct nature of this method, we explored whether SEEL can be accomplished in a single step by employing CMP-Neu5Ac modified by biotin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an engineered galactosyltransferase can selectively transfer UDP-N-a-azidoacetylgalactosamine (UDPGalNAz) to O-GlcNAc modified proteins. [18] Furthermore, it has been shown that GDP-6-azidofucose is readily accepted by a recombinant H. pylori a(1,3)-fucosyltransferase, and this has been successfully employed to image glycans in the enveloping layer of zebrafish embryos. [19] The attraction of enzymatic labeling is that it affords near quantitative labeling, does not perturb signaling pathways, and is amenable to all cell types.…”
mentioning
confidence: 99%
“…It could also catalyze the transfer of 2-C-acetyl-modified Gal from UDP-Gal2CAc ( 8 ) and was found to be useful in labeling GlcNAc-modified glycoproteins [45, 46]. The Y289L/M344H β4GalT1 double mutant combined the metal cofactor switch effect of the M344H mutation with the Gal2CAcT activity of the Y289L mutation to allow tagging and labeling of live cell surface glycans in the presence of more tolerable Mg 2+ instead of using potentially cytotoxic levels of Mn 2+ needed by the wild-type β4GalT1 [47]. Arg-228 is located near Glu-317, which forms a hydrogen bond between the 4-OH of the Gal in UDP-Gal and is required for the GalT activity [48], and the R228K mutation resulted in 15-fold higher GlcT activity which is further enhanced in the presence of α-lactalbumin to achieve 25% of the wild-type GalT activity [49].…”
Section: Structure-based Rational Design Of Glycosyltransferasesmentioning
confidence: 99%